2016
DOI: 10.5216/rpt.v45i4.44607
|View full text |Cite
|
Sign up to set email alerts
|

Perfil De Pacientes Com Linfedema Atendidos No Serviço De Referência Nacional Em Filarioses Da Fundação Oswaldo Cruz, Pernambuco, Brasil

Abstract: A filariose linfática é uma parasitose endêmica em 73 países e afeta, aproximadamente, 120 milhões de pessoas em todo o mundo. Este trabalho buscou traçar o perfil de pacientes com linfedema que residem em áreas endêmicas de filariose, com ou sem diagnóstico comprovado de doença prévia. Trata-se de um estudo transversal que envolveu pacientes com linfedema, cadastrados no SRNF-CPqAM-FIOCRUZ-PE, residentes nas principais cidades da região metropolitana de Recife, capital do estado de Pernambuco, aos quais foi a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…In view of this, we stress the importance of controlling the chronic condition with appropriate treatment, which can make a positive contribution to quality of life in this population. 5 These patients had associated comorbidities, in line with the literature, 5,26,27 confirming that they are common in people with severe lymphatic dysfunction. 28 Arterial hypertension, obesity, and diabetes were the most common comorbidities, as in a study by Santana et al, 26 who state that if these conditions are not controlled they facilitate development of sequelae.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In view of this, we stress the importance of controlling the chronic condition with appropriate treatment, which can make a positive contribution to quality of life in this population. 5 These patients had associated comorbidities, in line with the literature, 5,26,27 confirming that they are common in people with severe lymphatic dysfunction. 28 Arterial hypertension, obesity, and diabetes were the most common comorbidities, as in a study by Santana et al, 26 who state that if these conditions are not controlled they facilitate development of sequelae.…”
Section: Discussionsupporting
confidence: 73%
“…5 These patients had associated comorbidities, in line with the literature, 5,26,27 confirming that they are common in people with severe lymphatic dysfunction. 28 Arterial hypertension, obesity, and diabetes were the most common comorbidities, as in a study by Santana et al, 26 who state that if these conditions are not controlled they facilitate development of sequelae. Soares et al 5 reported these three comorbidities in a clinical study of patients with lymphedema living in an area where filariasis is endemic.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Twenty-eight patients were included in follow-up care at the outpatient clinic of the National Reference Service for Filariasis at the Oswaldo Cruz Foundation in Pernambuco - Brazil. This service is the only one in the country, linked to the health public system, the Sistema Único de Saúde (SUS), which ranges from primary care to complex procedures, that provides multidisciplinary assistance in the investigation and follow-up of patients with morbidity from an endemic area of lymphatic filariasis ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, in the bandaging step, a study was made (Soares et al, 2016;Santana et al, 2016) of the best fabric to be applied after CDT. An attempt was made to combine the resistance of the fabric with its low cost.…”
Section: Case Reportmentioning
confidence: 99%